Potential immunomodulatory effects of the extract from Artemisia frigida Willd on loaches infested with Aeromonas hydrophila revealed by microRNA analysis - Zhao, Yue; Qiu, Yuqing; Dai, Lishang; Wang, Hong (Frontiers in Genetics, 2025)
Artemisia frigida Willd is the most widely distributed Artemisia plant in the steppe and has a long history of medicinal applications in folk, especially as Mongolian medicine. Modern pharmacological research shows it exhibites biological activities such as antioxidant, anti-inflammatory and antibacterial. However, antibacterial applications of A. frigida in fish have not been reported. Loach is a kind of small economic fish with delicious meat and high nutritional value, which has high market value and demand in China. Nowadays, loach aquaculture technology is more mature, but the effective prevention and control of bacterial infectious disease outbreaks still need to be solved, for example, infection with Aeromonas hydrophila can cause high prevalence and mass deaths, leading to huge economic losses. MicroRNAs (miRNAs) regulate many biological processes, including an important regulatory role in the antibacterial immune response in fish, and immune-associated miRNAs have now been identified in a wide range of fish species, but less research has been carried out on loach miRNAs. To identify miRNAs related to antibacterial immunity in loach and to understand the potential immunomodulatory mechanism of A. frigida, we infected both Artemisia-fed and non-Artemia-fed loaches with Aeromonas hydrophila, and then constructed two small RNA libraries using high-throughput sequencing technology. Bioinformatics analysis identified 924 and 923 conserved miRNAs in control and AF (Artemisia frigida) treated samples, respectively, and 30 (26 upregulated and 4 downregulated) differentially expressed miRNAs were screened. Six immune-related miRNAs were selected for fluorescence quantitative PCR used to verify the accuracy of the sequencing results. Further target gene prediction and functional analysis of 30 differential miRNAs showed that the target genes of these miRNAs were involved in the regulation of several innate and antibacterial immunity-related pathways, including endocytosis, apoptosis, phosphatidylinositol signaling system, RLR signaling pathway, TLR signaling pathway and NLR signaling pathway. This study helps to deepen the understanding of the mechanism of miRNA regulation of antibacterial immune response in loach, and provides new insights into the application of the Chinese herb A. frigida in fish.